Writing, Silence, and Well-Being - Robert P. Yagelski (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Two composing activities suggest that writing together in silence constitutes an ontological act that creates community and serves as an alternative to perpetuating the divisiveness of current political discourse.